PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN PADA BIDANG NANOSAINS DAN NANOTEKNOLOGI UNTUK GURU KIMIA SMA DI KABUPATEN ACEH TIMUR - Ratih Permana Sari; Jofrishal (Global Science Society, 2020)
The purpose of this Community Service activity is to provide training in making video learning based on nanoscience and nanotechnology in the classroom learning process for MGMP Chemistry teachers in East Aceh. Service participants are teachers who are members of the MGMP of Chemistry in East Aceh. For the purpose of service services and the availability of facilities and infrastructure, 25 teachers were taken. The training was held at the East Aceh Superior High School Laboratory for 4 days on 3-4 July 2019. The implementation of community service in general can be categorized as successful in terms of participant participation considering that from the 25 target participants invited who attended were 26 to 29 people. Participants felt that this dedication activity was very useful fordeveloping nanoscience and nanotechnology-based learning video media that they would use in learning in their respective schools. the participants felt that this dedication activity was very beneficial for them, because as educators they felt the need to develop learning videos based on nanoscience and nanotechnology as a medium for delivering learning messages. This media can help educators in integrating learning through virtual and face-to-face